The SAMI Galaxy Survey: Using concentrated star formation and stellar population ages to understand environmental quenching. Issue 3 (29th August 2022) - Wang(王迪), Di; Croom, Scott M; Bryant, Julia J; Vaughan, Sam P; Schaefer, Adam L; D'Eugenio, Francesco; Barsanti, Stefania; Brough, Sarah; Lagos, Claudia del P; Medling, Anne M; Oh, Sree; van de Sande, Jesse; et al.
ABSTRACT: We study environmental quenching using the spatial distribution of current star formation and stellar population ages with the full SAMI Galaxy Survey. By using a star formation concentration index [ C -index, defined as log10 ( r 50, H α / r 50, cont )], we separate our sample into regular galaxies ( C -index ≥−0.2) and galaxies with centrally concentrated star formation (SF-concentrated; C -index <−0.2). Concentrated star formation is a potential indicator of galaxies currently undergoing 'outside-in' quenching. Our environments cover ungrouped galaxies, low-mass groups ( M 200 ≤ 10 12.5 M⊙ ), high-mass groups ( M 200 in the range 10 12.5–14  M⊙ ) and clusters ( M 200 > 10 14 M⊙ ). We find the fraction of SF-concentrated galaxies increases as halo mass increases by 9 ± 2 per cent, 8 ± 3 per cent, 19 ± 4 per cent, and 29 ± 4 per cent for ungrouped galaxies, low-mass groups, high-mass groups, and clusters, respectively. We interpret these results as evidence for 'outside-in' quenching in groups and clusters. To investigate the quenching time-scale in SF-concentrated galaxies, we calculate light-weighted age ( Age L ) and mass-weighted age ( Age M ) using full spectral fitting, as well as the D n 4000 and H δA indices. We assume that the average galaxy age radial profile before entering a group or cluster is similar to ungrouped regular galaxies. At large radius (1–2 R e ), SF-concentrated galaxies in high-mass groups have older ages than ungrouped regular galaxies with an age difference of 1.83 ± 0.38 Gyr for Age L and 1.34 ± 0.56 Gyr for Age M . This suggests that while 'outside-in' quenching can be effective in groups, the process will not quickly quench the entire galaxy. In contrast, the ages at 1–2 R e of cluster SF-concentrated galaxies and ungrouped regular galaxies are consistent (difference of 0.19 ± 0.21 Gyr for Age L, 0.40 ± 0.61 Gyr for Age M ), suggesting the quenching process must be rapid.